2023
DOI: 10.1186/s12985-023-02034-x
|View full text |Cite|
|
Sign up to set email alerts
|

Morphological, biological, and genomic characterization of Klebsiella pneumoniae phage vB_Kpn_ZC2

Abstract: Background Bacteriophages (phages) are one of the most promising alternatives to traditional antibiotic therapies, especially against multidrug-resistant bacteria. Klebsiella pneumoniae is considered to be an opportunistic pathogen that can cause life-threatening infections. Thus, this study aims at the characterization of a novel isolated phage vB_Kpn_ZC2 (ZCKP2, for short). Methods The phage ZCKP2 was isolated from sewage water by using the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
3
4
0
Order By: Relevance
“…The killing curve also showed that the lytic activity of phage MKP-1 is MOI-dependent, and the higher MOI (MOI 10) was optimal for the greatest reduction of host cells. These findings are quite similar to the previously reported phages such as Klebsiella phage ZCKP2 ( Fayez et al, 2023 ), vB_KpnS_Kp13 ( Horváth et al, 2020 ) and P545 ( Li et al, 2020 ). The clear plaques produced on the bacterial lawn also ensure its lytic nature, nullifying it being a temperate phage.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The killing curve also showed that the lytic activity of phage MKP-1 is MOI-dependent, and the higher MOI (MOI 10) was optimal for the greatest reduction of host cells. These findings are quite similar to the previously reported phages such as Klebsiella phage ZCKP2 ( Fayez et al, 2023 ), vB_KpnS_Kp13 ( Horváth et al, 2020 ) and P545 ( Li et al, 2020 ). The clear plaques produced on the bacterial lawn also ensure its lytic nature, nullifying it being a temperate phage.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the growth curve of this phage, a high latent period (40 min) of the phage is often an indicator of high burst size ( Abedon et al, 2001 ), confirming its effective use as therapeutics. The large burst size (more than 200 pfu per cell) is comparable to other Klebsiella phages such as phage KP 1801 and ZCKP2 ( Wintachai et al, 2020 ; Fayez et al, 2023 ). However, unlike phage MKP-1, other Siphoviridae Klebsiella phages have been shown to have a latent period of approximately 20 min ( Horváth et al, 2020 ; Fayez et al, 2023 ).…”
Section: Discussionmentioning
confidence: 73%
“…A slight decrease in stability was observed at pH 12 with no ability to detect phages at pH 2, 3, and 13 (Figure 3). The stability of our isolated phage at different values of pH indicated that the phage can withstand harsh conditions as indicated before [50,75,72,76,77,78] and this is considered an added value since the optimal minimum pH for most cheese manufacturing is in the range of (5.0 -5.3) [79]. Such characteristics enable the use of phage in industrial applications since the stretching properties of cheese, melting, and texture can be influenced by many factors, including cheese composition, Ca content, salt content, protocols of manufacturing, and pH [80].…”
Section: Phage Stabilitysupporting
confidence: 57%
“…Phages from the collection showed a narrow host range, in most cases affecting different strains of the same bacterial species. Bacteriophages can replicate in two ways once attached to the host: lytically and lysogenically (8,9) . Bacteria can protect themselves against the attack of bacteriophages in various ways.…”
Section: Introductionmentioning
confidence: 99%